Some Problems Arising from Defining Lyric Poetry (Damascus University Journal of arts and humanities sciences, 2021)
This paper discusses the nature of lyric, one of the three general categories of poetic literature. It attempts to define the lyric’s parameters by investigating David Lindley’s definition of lyric through its relation to music, when he states that “the poem written to be sung remains the one to which no critic can deny the label ‘lyric’”. Expanding Lindley’s definition, the paper will suggest that Lindley’s definition problematises our notion of lyric. Then it moves on to examine the various critical analyses of lyric according to some critical theories which challenge lyric’s musicality as an aesthetically intrinsic feature.
Keywords: Some Problems Arising from Defining Lyric Poetry